Saturday

April 19, 2014

April 19, 2014

Posted by **vicki** on Sunday, October 9, 2011 at 12:11pm.

- calculus -
**Steve**, Sunday, October 9, 2011 at 6:35pmIf you mean (x^2+1) * (x^2+2)^(1/3) then just use the product rule and chain rule.

y = u*v^n

y' = u'v^n + u*n*v^(n-1)*v'

u = x^2 + 1

u' = 2x

v = x^2 + 2

v' = 2x

y' = 2x*cbrt(x^2+2) + 2x*(x^2+1)* 1/3 * (x^2 + 2)^(-2/3)

Feel free to simplify further. You're doing calculus; algebra should be a breeze.

**Related Questions**

Calculus - Any help would be much appreciated with the steps involved in each ...

Calculus - Any help would be much appreciated with the steps involved in each ...

Calculus I - Find the derivative ** (sq root) y = (square root) x + (2nd sq root...

Chain Rule - Any help would be much appreciated with the steps involved in each ...

Calculus - find derivitive of 1/square root of x 1/square root of x = x^(-1/2) ...

Maths Calculus Derivative Integral - Urgent Please - Use 2nd Fundamental Theorem...

Calculus - How do i find the derivative of f(t)= 20- 30/rooot 9 + t^2 heres how ...

math, calculus - find the derivative of the function y= integral from square ...

Calculus/Logarithms - Find the derivative of f(x) = (square root of x)(ln x). ...

Calculus - How do you find the derivative of (x+1) times the third root of (x-5)...